1998
DOI: 10.1097/00006534-199811000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Foot and Ankle Reconstruction Using the Radial Forearm Flap: A Review of 25 Cases

Abstract: Twenty-five patients underwent soft-tissue reconstruction of the different anatomic regions of the foot and ankle using the microvascular radial forearm free flap. The patients, 19 men and 6 women, ranged in age from 3 to 80 years (mean, 48.4 years). Indications for the surgery included diabetes and/or vascular insufficiency (10 patients), trauma (9 patients), tumor (3 patients), gunshot wound (2 patients), and burn (1 patient). Osteomyelitis occurred in patients with traumatic (3 patients) and diabetic (3 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 16 publications
1
67
0
3
Order By: Relevance
“…[24][25][26] However, fasciocutaneous flaps are advantageous in superficial defects without bony irregularities, because they are thin and pliable and provide better sensation. [27][28][29] Protective sensation is important for flap durability in weight-bearing areas, and has repeatedly been reported in muscle flaps and fasciocutaneous flaps alike. 28,[30][31][32] However, the debate about innervated flaps for reconstruction of plantar defects is controversial.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[24][25][26] However, fasciocutaneous flaps are advantageous in superficial defects without bony irregularities, because they are thin and pliable and provide better sensation. [27][28][29] Protective sensation is important for flap durability in weight-bearing areas, and has repeatedly been reported in muscle flaps and fasciocutaneous flaps alike. 28,[30][31][32] However, the debate about innervated flaps for reconstruction of plantar defects is controversial.…”
Section: Discussionmentioning
confidence: 97%
“…Although tactile sensation is clearly superior in fasciocutaneous flaps, this does not appear to be necessary to maintain an intact and functional plantar surface. 27,28,[30][31][32] Nevertheless, flaps transferred to insensate areas are more prone to damage because of the lack of deep pressure sensation and unfavorable weight distribution. 32 Patients with impaired sensation may therefore benefit from innervated flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular fasciocutaneous flaps have become increasingly popular for reconstruction of the foot because they tend to be thin, limiting the bulkiness of the reconstruction [24]. Some examples of fasciocutaneous flaps that can provide stable and aesthetic coverage of the foot include a radial forearm flap, a scapula flap, an anterolateral thigh flap and a lateral arm flap.…”
Section: Surgical Planningmentioning
confidence: 99%
“…Although Weinzweig and Davies http://gateway. ut.ovid.com/gw2/-60 [24] indicated that sensory reinnervation may be beneficial, they were not sure if the addition of sensation to the foot would protect against wound breakdown. Other studies have http://gateway.…”
Section: Surgical Planningmentioning
confidence: 99%
“…Lower extremity defects can also be reconstructed with free fasciocutaneous flaps (179,191). Such flaps consist of skin, subcutaneous tissue and fascia.…”
Section: Free Radial Forearm Flapmentioning
confidence: 99%